Theoretical studies of 63Cu2+ orbital Knight shifts of HgBa2Ca2Cu3O8+δ - Kuang, Min-Quan; Wu, Shao-Yi; Hu, Xian-Fen (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
The orbital Knight shifts and g factors for the tetragonal 63Cu2+ site in HgBa2Ca2Cu3O8+δ at 133 and 115 K are theoretically investigated based on the high-order perturbation formulae of these quantities for a 3d9 ion situated into tetragonally elongated octahedra. The theoretical results reveal good agreement with the observed values. The significant anisotropies of the Knight shifts are illustrated as the considerable local tetragonal elongation distortions of the five-coordinated Cu2+sites. The results at different temperatures are also discussed in viewof the local structure of the Cu2+ sites.